HISTORICAL DEVELOPMENT AND ARCHITECTURAL FEATURES OF KULA ZAFER SCHOOL IN THE CONTEXT OF GREEK SCHOOL - Baş, Gizem Özer; Demir, İpek; Gölükcü, İpek (Fırat University, 2024)
During the Ottoman period, a high proportion of Greek population lived in the Kula district of Manisa province. It is possible to understand the reflection of the abundance and influence of the Greek population from the existence of three Greek schools in a rural settlement like Kula in the 19th century. One of these schools is Zafer School, which is the subject of the study. The aim of the study is to introduce the Zafer School, which is not included in the academic literature, into the literature as a cultural heritage and to document it as a typological example. Within the scope of this article, firstly the history and cultural diversity of Kula was examined in order to introduce the settlement, and then the establishment, functioning, legal status and architectural features of the Greek schools were explained in order to describe the historical process and architectural features of the Zafer School. Within the scope of these limitations, the study was examined in line with information obtained from various sources, close areas, and archives. The architectural features and current situation of the school are revealed in line with the observations made during the field research and the drawings created afterwards. Within the framework of the current situation, evaluations were made in the context of architectural restoration and recommendations were explained.

Osmanlı Döneminde Manisa ili Kula ilçesinde yüksek oranda Rum nüfus yaşamaktaydı. Rum nüfusun fazlalığının ve etkisinin yansımasını 19. yüzyılda Kula gibi kırsal bir yerleşimde üç adet Rum mektebinin var olmasından anlamak mümkün olabilir. Bu mekteplerden biri çalışmanın konusunu oluşturan Zafer Okulu’dur. Çalışmanın amacı akademik yazında yer almayan, bulunmayan Zafer Okulu’nun kültürel miras olarak literatüre kazandırılması ve tipolojik bir örnek olarak belgelendirilmesidir. Makalede öncelikle yerleşimi tanıtmak amacı ile Kula’nın tarihçesi ve kültürel çeşitliliği irdelenmiş ve ardından Zafer Okulu’nun tarihsel süreci ve mimari özelliklerini tanımlamak için Rum okullarının kuruluş, işleyiş, yasal durumları ve mimari özellikleri bu kapsamda detaylı bir biçimde aktarılmıştır. Çalışma tüm bu sınırlılıklar kapsamında çeşitli nitelikteki kaynaklar, kişiler, yakın çevre ve arşivlerden elde edilen bilgiler doğrultusunda ortaya çıkmaktadır. Saha araştırmalarında yapılan gözlemler ve ardından oluşturulan çizimler doğrultusunda bu okulun mimari özellikleri, tüm tarihi dökümanı ve günümüzdeki durumu ortaya koyulmaktadır. Bu kapsamda mevcut durum çerçevesinde mimari restorasyon bağlamında tarafsız değerlendirmeler yapılarak öneriler açıklanmıştır.
RUM MEKTEPLERİ BAĞLAMINDA KULA ZAFER OKULU’NUN TARİHSEL GELİŞİMİ VE MİMARİ ÖZELLİKLERİ
Keywords: Environment and Culture; Çevre ve Kültür